2023
DOI: 10.3390/microorganisms12010034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Potential Anti-Methanogenic and Antimicrobial Activity of Ethyl Nitroacetate, α-Lipoic Acid, Taurine and L-Cysteinesulfinic Acid In Vitro

Gizem Levent,
Aleksandar Božić,
Branko T. Petrujkić
et al.

Abstract: Livestock producers need new technologies to maintain the optimal health and well-being of their animals while minimizing the risks of propagating and disseminating pathogenic and antimicrobial-resistant bacteria to humans or other animals. Where possible, these interventions should contribute to the efficiency and profitability of animal production to avoid passing costs on to consumers. In this study, we examined the potential of nitroethane, 3-nitro-1-propionate, ethyl nitroacetate, taurine and L-cysteinesu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Moreover, we found sulfur-containing amine taurine in the serum was lowered in the PEO group. Taurine is known to function as an anaerobic electron acceptor [ 50 ], a recent study reported taurine supplementation reduced CH 4 production in vitro [ 51 ]. During sulfur metabolism, taurine can degrade into sulfide, which serving as an alternative H 2 sink [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found sulfur-containing amine taurine in the serum was lowered in the PEO group. Taurine is known to function as an anaerobic electron acceptor [ 50 ], a recent study reported taurine supplementation reduced CH 4 production in vitro [ 51 ]. During sulfur metabolism, taurine can degrade into sulfide, which serving as an alternative H 2 sink [ 47 ].…”
Section: Discussionmentioning
confidence: 99%